Heuristic Method of G. Polya in the Opinion of the Early-School Education Teachers - Ewelina Kawiak (Vasyl Stefanyk Precarpathian National University, 2024)
The proposed text discusses the issue of teaching mathematics at the first educational stage. Effective mathematics education is crucial for developing thinking skills and dealing with problem solving in everyday life. Pedagogical practice shows that problem-based methods are one of the most effective methods of teaching this subject. Taking into account the educational value of problem-based teaching methods, the heuristic method of G. Polya was particularly emphasized in the text. The method, created by a Hungarian scientist, is used to solve tasks. Solving problems, in turn, is one of the most important competencies developed during mathematics education. The examples of how the method has been used so far when working with younger pupils were demonstrated in the text below. The noticeable shortage of Polish literature regarding the application of this method when working with students of younger school age, encouraged the author to deeply reflect upon the current state of affairs. The article contains the results of the survey regarding the knowledge of G. Polya's method among early-school education teachers. The research was conducted in primary schools located in the Silesian Voivodeship. The study has attempted to define the opinions of the surveyed teachers with regard to the method and to establish what they consider to be the possibilities of using it in early-school education. The obtained research results show that despite many educational values, the described method is not very popular among the respondents. Therefore, it can be concluded that its capabilities are not used to a sufficient extent. These results encourage further reflection on possible ways of popularizing problem-based methods among professionally active teachers and among students preparing to work with students of early school age.